2013
DOI: 10.1111/echo.12409
|View full text |Cite
|
Sign up to set email alerts
|

Severe Mitral Regurgitation after Radiotherapy

Abstract: We present the case of a 69-year-old patient with a history of gynecological neoplasia and a pulmonary metastasis, who in 1996 underwent chemotherapy and mediastinal radiotherapy followed by cancer remission. Ten years later she presented with heart failure and her Doppler echocardiogram showed severe mitral regurgitation with pulmonary hypertension. In 2011, she underwent a mitral valve replacement with a biological prosthesis and the pathology exam revealed valve damage consistent with radiotherapy-induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…In keeping with clinical investigators [9,10] we hypothesise that the observed effects may be due to the presence of critical vascular structures including the aorta, superior vena cava and coronary arteries, or pacemaker tissues central to the cardiac conduction system including the sinoatrial and atrioventricular nodes. Cardiac structures located in sub-volumes of that heart shown to be radiosensitive in clinical studies are summarized in table 1 [10,[19][20][21][22][23][24][25][26]. In addition, the atria located in the base, also have important endocrine functions mediated by hormones including cardiac natriuretic peptides, and adrenomedullin, which work to coordinate the function of other cardiovascular organs [27], and may be impacted by radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with clinical investigators [9,10] we hypothesise that the observed effects may be due to the presence of critical vascular structures including the aorta, superior vena cava and coronary arteries, or pacemaker tissues central to the cardiac conduction system including the sinoatrial and atrioventricular nodes. Cardiac structures located in sub-volumes of that heart shown to be radiosensitive in clinical studies are summarized in table 1 [10,[19][20][21][22][23][24][25][26]. In addition, the atria located in the base, also have important endocrine functions mediated by hormones including cardiac natriuretic peptides, and adrenomedullin, which work to coordinate the function of other cardiovascular organs [27], and may be impacted by radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…No espessamento valvar mitral por radiação, nota-se espessamento da valva associada a histórico de neoplasia e radioterapia torácica. 3 Essas patologias definem a maioria das regurgitações mitrais primárias. Caso não se identifique alteração estrutural da valva mitral -mas sim dilatação e disfunção ventricular esquerda, como ocorre na cardiomiopatia dilatada com dilatação do anel valvar e refluxo mitral secundário -e nem alteração contrátil da parede inferior ou inferolateral por infarto do miocárdio com comprometimento da coaptação da cúspide posterior mitral, então a definição passa a ser de insuficiência mitral secundária, cujo problema valvar é consequência, e não causa.…”
Section: Avaliação Da Valva Mitral: Como Eu Faço?unclassified
“…The patient also received chemotherapy (doxorubicin and cisplatinum) and local radiotherapy (50 Gy) because of a single lung metastasis, with total remission during later follow-up. About 10 years later following radiotherapy, she had increasing breathlessness and a new pansystolic murmur at the left sternal edge and progressed insidiously to retrograde left heart failure [1].…”
Section: Case Reportmentioning
confidence: 99%